Preparation method and application of nano tunneling layer

By using nitrogen and oxidizing gas plasma treatment technology, oxygen-containing silicon nitride films are prepared, which solves the problems of uneven thickness of the nanotunnel layer and fast growth rate, and achieves more stable battery efficiency and higher product yields.

CN119907330APending Publication Date: 2025-04-29NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311379416.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art has problems of uneven thickness, fast growth rate and high annealing temperature when preparing nanotunnel layers, resulting in fluctuations in battery efficiency and product yields.

Method used

A mixed gas of nitrogen and oxidizing gas is used for plasma treatment to form an oxygen-containing silicon nitride film. By controlling the gas flow ratio, discharge time and reaction pressure, the growth rate and thickness variance of the nanotunnel layer are reduced.

Benefits of technology

The thickness growth rate and thickness variance of the nanotunnel layer are significantly reduced, the uniformity of the layer is improved, the battery efficiency is stabilized, and the energy consumption of high-temperature annealing is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907330A_ABST
    Figure CN119907330A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a nanometer tunneling layer, and the preparation method of the nanometer tunneling layer comprises the following steps: S1, cleaning a silicon wafer through employing cleaning liquid with oxidability, and generating a wet-process original oxide layer; s2, the silicon wafer is placed in a quartz boat of tubular PECVD, reaction gas is introduced for heat preservation, and the reaction gas is mixed gas of nitrogen and oxidizing gas; and S3, continuously introducing the reaction gas, carrying out plasma treatment, dissociating the reaction gas, nitriding the surface of the silicon wafer, and forming an oxygen-containing silicon nitride film. According to the method, nitrogen and oxygen-containing gas are used as reaction gases, the prepared nano tunneling layer is made of oxygen-containing silicon nitride, and compared with a silicon oxide thin film, the self-saturation thickness of the thin film is reduced, so that the thickness increasing rate of the thin film is reduced, and overall uniformity control is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a preparation method of a nano tunneling layer and application thereof. Background Art

[0002] The tunneling silicon oxide passivation contact structure (TOPCon) is a new type of crystalline silicon solar cell structure first proposed by the Fraunhofer Institute in Germany in 2013. The core of this structure is to use an ultra-thin silicon oxide layer and a doped polysilicon stacked structure to passivate the silicon wafer surface. At present, TOPCon cells have been industrialized. The typical preparation process steps of N-type TOPCon cells are as follows: a boron emitter is formed on the front of the N-type silicon wafer, and then a layer of ultra-thin silicon oxide with a thickness of less than 3nm is grown on the back. A layer of phosphorus-doped amorphous silicon or polysilicon is deposited on the silicon oxide by PECVD, and doped polysilicon is formed after heat treatment; then a surface passivation film and an anti-reflection film are deposited, and finally a silver paste is screen-printed and sintered to form a gate.

[0003] The nano-tunneling layer in the TOPCon battery has a key influence on its performance. Parameters such as the thickness and quality of the tunneling layer directly determine the efficiency and yield of mass-produced batteries. In mass production technology, the tubular PECVD technology route is one of the mainstream technology routes, with a market share of more than 50%. The method of preparing the nano-tunneling layer using tubular PECVD is as follows: the silicon wafer is cleaned with a chemical reagent (currently a H2O2 aqueous solution is commonly used), the silicon wafer is placed on a graphite boat and placed in a quartz tube, and the laughing gas (N2O) is introduced as a gas source, and then the plasma power supply (40kHz) is turned on for discharge to form a plasma based on a pure laughing gas source, and the oxygen source in the plasma is used to oxidize the silicon surface to form a nano-silicon oxide layer. This method is simple and efficient and has been widely used in the industry. However, there are also significant technical difficulties in preparing the nano-oxide layer using tubular PECVD, the main manifestations of which include: the thickness of the nano-oxide layer is uneven, and various thickness fluctuations are easily generated between tubes and batches. The thickness variance is greater than 5% when measured using an ellipsometer, resulting in fluctuations in battery efficiency and a decrease in product yield.

[0004] The thickness growth curve of the nano tunneling layer in the existing process is as follows: Figure 1 As shown (thickness is calibrated using an ellipsometer), according to the analysis, the main problems are as follows:

[0005] (1) The existing silicon oxide layer preparation process has a large saturated thickness of silicon oxide (corresponding to Figure 1Δt1 part). When using PECVD technology and using N2O as an oxygen source to prepare an ultra-thin silicon oxide layer, the oxidation process will pass through a rapid oxidation area, then tend to be gentle and gradually reach the oxidation saturation area, and the process interval is mainly concentrated in the rapid oxidation area. The oxidation speed in this area is very fast and difficult to control accurately. The saturation thickness of silicon oxide prepared under existing oxidation conditions is about 4nm; if the thickness of the oxide layer does not reach this thickness, the oxide layer will grow at a relatively fast rate under discharge conditions. In actual industrial applications, the thickness of the oxide layer needs to be controlled in the range of 1.6-1.8nm, which makes the process control very difficult. If you are not careful, the thickness of the oxide layer will exceed the reasonable thickness range. In addition, since the existing preparation process cannot make the silicon oxide thickness enter the oxidation saturation area in a short time, it is also easy to cause uneven thickness. This is because the growth rate of the silicon oxide layer in different areas of the silicon wafer is different due to the influence of the silicon oxide preparation equipment. Due to the lack of the self-saturation effect on the balancing effect of the oxide layer thickness, the silicon oxide everywhere will be in a rapid growth stage and cannot maintain a uniform growth on the same time line. The large fluctuations caused by this process will lead to uneven silicon oxide thickness. The saturated thickness of silicon oxide in the existing process is relatively thick. If the oxidation time is increased in pursuit of uniformity, it is easy to cause the silicon oxide layer to be too thick, and the doped layer cannot diffuse to the substrate to achieve a good passivation effect.

[0006] (2) The thickness growth rate of the oxide layer in the initial stage of oxide layer growth is fast (corresponding to Figure 1 When nitrous oxide plasma is used as the oxygen source, the oxygen source concentration ratio in the plasma is still high and the oxidation rate is fast. In addition, under pure nitrous oxide conditions, the main component of the deposited silicon oxide is SiO x Due to the large porosity of the silicon oxide dielectric layer, the diffusion rate of oxygen atoms in it is also high, which is one of the main reasons for the fast growth rate of the oxide layer. Within the actual process time range, the thickness of the oxide layer can change by 0.1-0.2nm every 30 seconds, which is a significant change. However, a faster oxidation rate can easily lead to a faster increase in the thickness of the oxide layer in different areas, which is not conducive to overall uniformity control.

[0007] (3) The thickness of the wet native oxide layer fluctuates greatly (corresponding to Figure 1 Before silicon oxide is grown on the surface of the silicon wafer, the surface is cleaned by a wet chemical method containing H2O2. The thickness of the surface oxide layer produced by the cleaning liquid in the new preparation stage and the stage near the liquid change is different, usually with a difference of about 0.1-0.2nm. This fluctuation will cause the thickness of the silicon oxide obtained to fluctuate greatly under the same plasma discharge preparation process conditions, resulting in a significant dispersion of battery performance, reducing battery efficiency and yield.

[0008] (4) The existing tunneling layer annealing temperature is relatively high. After preparing the tunneling layer and the amorphous silicon layer, a high-temperature annealing process is required. Due to the fast growth rate, high saturation thickness and large thickness fluctuation of the existing tunneling layer, the high-temperature annealing process not only has an unstable temperature, but also requires a relatively high annealing temperature, which leads to an increase in the energy consumption required for battery production. Summary of the invention

[0009] In view of the deficiencies of the prior art, the technical problem to be solved by the present invention is how to effectively control the growth of the nano-tunneling layer and improve the thickness uniformity, thereby stabilizing the battery efficiency and improving the product yield.

[0010] In order to solve the above problems, the present invention provides a method for preparing a nano tunneling layer, comprising the following steps:

[0011] S1, using an oxidizing cleaning liquid to clean the silicon wafer to produce a wet native oxide layer;

[0012] S2, placing the silicon wafer in a tubular PECVD quartz boat, introducing a reaction gas for heat preservation, wherein the reaction gas is a mixture of nitrogen and an oxidizing gas;

[0013] S3. Continue to introduce the reaction gas to perform plasma treatment to dissociate the reaction gas, nitriding the surface of the silicon wafer to form an oxygen-containing silicon nitride film.

[0014] The present invention uses nitrogen and oxidizing gas as reaction gases, and the material of the prepared nano-tunneling layer is oxygen-containing silicon nitride. Compared with silicon oxide film, the lattice of silicon nitride has more significant rigidity characteristics, and the difficulty for impurity atoms including nitrogen atoms and oxygen atoms to pass through the silicon nitride film increases, and the diffusion coefficient is significantly reduced, thereby reducing the thickness growth rate of the oxygen-containing silicon nitride film, which is beneficial to controlling the uniformity of the film thickness; silicon nitride contains a small amount of oxygen, and the presence of oxygen has a good passivation effect on interface state defects, so the oxygen-containing silicon nitride layer material has a good surface passivation effect.

[0015] Furthermore, in the steps S2 and S3, the flow ratio of nitrogen to oxidizing gas is greater than or equal to 5:1, preferably 10:1. Nitrogen is the main component in the reaction gas, and the saturated thickness of the deposited oxygen-containing nano-silicon nitride film is significantly lower than the saturated thickness of the nano-silicon oxide, thereby reducing the film thickness growth rate.

[0016] Furthermore, the oxidizing gas is selected from at least one of nitrous oxide, carbon dioxide and oxygen.

[0017] Furthermore, in step S3, the discharge pulse time in one pulse cycle during the plasma discharge process is less than 2ms, preferably less than 1ms. The low discharge time is combined with the ultra-low duty cycle discharge mode and the higher gas flow ratio to significantly suppress the growth rate of the nano tunneling layer.

[0018] Furthermore, in step S3, the reaction pressure is greater than or equal to 140Pa.

[0019] Furthermore, in step S3, during the plasma discharge process, the thickness of the silicon nitride film increases by no more than 0.1 nm every 30 seconds, and its saturation thickness is less than 2.5 nm, which significantly reduces the growth rate of the silicon nitride film, broadens the process window, and is conducive to improving the uniformity of the nanotunneling layer.

[0020] Furthermore, in step S3, an intermittent discharge mode is adopted, and discharge and stop discharge are performed alternately. The intermittent discharge mode can better maintain the growth rate of the film thickness and avoid the nano-tunneling layer thickness in some areas increasing too fast.

[0021] Furthermore, in step S2, the insulation temperature is 200-600° C., and the insulation time is 30-300 seconds.

[0022] Furthermore, in step S2, a thermal oxide layer with a fixed thickness, typically 1.4±0.05 nm, is formed on the surface of the silicon wafer. The thickness may fluctuate to a certain extent depending on the holding temperature.

[0023] The thickness of the wet oxide layer usually has large fluctuations. Before plasma discharge, a thermal oxide layer is formed on the surface of the silicon wafer. The thickness of the thermal oxide layer has nothing to do with the original thickness of the wet native oxide layer, but is only related to the temperature. This step can effectively suppress the thickness fluctuation of the wet native oxide layer and significantly stabilize the initial thickness of the film on the surface of the silicon wafer before depositing the silicon nitride film.

[0024] The present invention also provides an application of the above-mentioned method for preparing the nano-tunneling layer, and the preparation method is used for preparing TOPCon solar cells. Due to the overall rate reduction, the thickness variance of the nano-tunneling layer prepared by the present invention is less than 4%, which has good uniformity and is conducive to improving the cell efficiency and production yield.

[0025] Furthermore, in the process of preparing TOPCon solar cells, the annealing temperature of the nano tunneling layer is 800-1000° C. The tunneling layer prepared by the process of the present invention has a low growth rate, and the prepared tunneling layer is very uniform, which can reduce the temperature of the subsequent high-temperature annealing process by 20-30° C.

[0026] In summary, the present invention has the following beneficial effects compared with the prior art:

[0027] (1) The present invention uses nitrogen and oxidizing gas as reaction gases and oxygen-containing silicon nitride film as nano-tunneling layer. The nitrogen ratio in the reaction gas is high. The main component of the film is silicon nitride, and the self-saturation thickness is only about 2.5nm, which is significantly lower than the self-saturation thickness of silicon oxide. Therefore, the growth rate of the film thickness is reduced, which is beneficial to the overall uniformity control.

[0028] (2) The present invention comprehensively utilizes a low discharge time combined with an ultra-low duty cycle discharge mode and a higher gas flow ratio to significantly suppress the growth rate of the nano-tunneling layer, thereby precisely controlling the thickness of the nano-tunneling layer.

[0029] (3) Before the discharge generates plasma, the present invention first introduces the reaction gas and keeps it at the process temperature for a period of time to achieve surface nitridation of the silicon wafer, smooth the thickness fluctuation of the wet native oxide layer, and thus improve the thickness uniformity of the nano-tunneling layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the thickness growth curve of the nano-tunneling layer in the existing process and the existing problems;

[0031] Figure 2 The saturated thickness growth curve and film forming rate curve of the thin films prepared in Example 1, Example 2 and Comparative Example 1 of the present invention;

[0032] Figure 3 The graph is a thickness growth curve of the thin film on the surface of the silicon wafer of Example 3, Example 4 and Comparative Example 2 of the present invention;

[0033] Figure 4 This is a thickness growth curve of the thin film silicon nitride film prepared in Example 1, Example 2 and Example 5 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0035] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0036] An embodiment of the present invention provides a method for preparing a nano tunneling layer, comprising the following steps:

[0037] S1, using an oxidizing cleaning liquid to clean the silicon wafer to produce a wet native oxide layer;

[0038] S2, placing the silicon wafer in a tubular PECVD quartz boat, passing the reaction gas for heat preservation, the reaction gas is a mixture of nitrogen and oxidizing gas, wherein the oxidizing gas is commonly but not limited to nitrous oxide, carbon dioxide, oxygen, etc., to form a thermal oxide layer on the surface of the silicon wafer. In a specific embodiment, the insulation temperature is 200-600°C, the insulation time is 30-300 seconds, and the thickness of the thermal oxide layer is a fixed value, which is commonly 1.4±0.05nm. This step can effectively suppress the thickness fluctuation of the wet native oxide layer, and significantly stabilize the initial thickness of the film on the surface of the silicon wafer before the deposition of the silicon nitride film.

[0039] S3, continue to introduce the reaction gas, perform plasma treatment, dissociate the reaction gas, nitride the surface of the silicon wafer, and form an oxygen-containing silicon nitride film. The flow ratio of nitrogen to oxidizing gas is greater than or equal to 5:1, preferably 10:1, the reaction gas is mainly composed of nitrogen, and the thickness of the deposited oxygen-containing nano silicon nitride film is significantly lower than the saturated thickness of nano silicon oxide, thereby reducing the film thickness growth rate.

[0040] In a specific embodiment, in a pulse cycle during plasma discharge, the discharge pulse time is less than 2ms, preferably less than 1ms; the reaction pressure is greater than or equal to 140Pa, and the low discharge time is combined with the ultra-low duty cycle discharge mode, higher gas flow ratio, and higher reaction pressure to significantly suppress the growth rate of the nanotunneling layer. During the plasma discharge process, the thickness of the silicon nitride film increases by no more than 0.1nm every 30sec, and its saturation thickness is less than 2.5nm.

[0041] Step S3 preferably adopts an intermittent discharge mode, in which discharge and stop discharge are performed alternately. The intermittent discharge mode can better maintain the growth rate of the film thickness and avoid the rapid increase of the thickness of the nano-tunneling layer in some areas.

[0042] The above method reduces the saturation thickness of the nano-tunneling layer material, adopts a discharge mode with a low discharge time combined with an ultra-low duty cycle, reduces the film thickness growth rate, and combines the step of generating a thermal oxidation layer to control the thickness of the film from multiple aspects, broaden the process window, and improve the uniformity of the nano-tunneling layer. The thickness variance of the nano-tunneling layer prepared by the above method is less than 4%. The above method for preparing the nano-tunneling layer is used in the preparation of TOPCon solar cells, which is conducive to improving the cell efficiency and production yield.

[0043] The technical solutions and effects of the present invention are described below through specific embodiments.

[0044] Example 1

[0045] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0046] 2) Place the silicon wafer in PECVD, introduce N2:N2O=10:1, perform plasma treatment, discharge duty cycle is 1ms:200ms, nitridation temperature is 430℃, and reaction time is 120sec;

[0047] 3) Use an ellipsometer to measure the thickness growth curve of the silicon nitride film and calculate the film thickness growth rate.

[0048] Example 2

[0049] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0050] 2) Place the silicon wafer in PECVD, introduce N2:N2O=15:1, perform plasma treatment, discharge duty cycle is 1ms:200ms, nitridation temperature is 430℃, and reaction time is 120sec;

[0051] 3) Use an ellipsometer to measure the thickness growth curve of the silicon nitride film and calculate the film thickness growth rate.

[0052] Comparative Example 1

[0053] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0054] 2) Place the silicon wafer in PECVD, introduce pure N2O, and perform plasma treatment. The plasma discharge duty cycle is 1ms:200ms, the oxidation temperature is 430℃, and the reaction time is 120sec;

[0055] 3) Use an ellipsometer to measure the thickness growth curve of the silicon nitride film and calculate the film thickness growth rate.

[0056] Figure 2 The above figure shows the saturation thickness curves of the films prepared in Examples 1 and 2 and Comparative Example 1. From the comparison of the two curves, it can be seen that when a mixed gas with a high N2:N2O ratio is used as the reaction gas, the deposited oxygen-containing nano-silicon nitride layer has a low saturation thickness, and its saturation thickness is less than 2.5nm, which is significantly lower than the saturation thickness of the silicon oxide layer prepared by pure N2O. Figure 2The figure below shows the film forming rate curves of Examples 1 and 2 and Comparative Example 1. Examples 1 and 2 have higher rate stability. The average thickness of 60 sheets from 2 boats for Example 1 has a thickness uniformity of 1.37%; the average thickness of 60 sheets from 2 boats for Example 2 has a thickness uniformity of 1.47%.

[0057] Example 3

[0058] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0059] 2) Place the silicon wafer in PECVD, introduce N2:N2O=10:1, and the nitridation temperature is 430°C;

[0060] 3) Use an ellipsometer to measure the thickness growth curve of silicon nitride film.

[0061] Example 4

[0062] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0063] 2) Place the silicon wafer in PECVD, introduce N2:N2O=5:1, and the nitridation temperature is 430°C;

[0064] 3) Use an ellipsometer to measure the thickness growth curve of silicon nitride film.

[0065] Comparative Example 2

[0066] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0067] 2) Use an ellipsometer to measure the thickness growth curve of silicon nitride film.

[0068] Figure 3 The figure above shows that the thickness of the wet native oxide layer on the silicon wafer surface of Comparative Example 2 varies greatly from batch to batch; Figure 3 The figure below shows the thickness growth curve of oxygen-containing silicon nitride in Examples 3 and 4 under non-discharge conditions, with a small fluctuation range, which significantly stabilizes the initial thickness of the native oxide layer.

[0069] Example 5

[0070] 1) Prepare a 182mm×182mm silicon wafer and perform standard cleaning on the silicon wafer using a liquid containing H2O2;

[0071] 2) Place the silicon wafer in PECVD, introduce N2:N2O=10:1, nitridation temperature is 430℃, reaction time is 120sec;

[0072] 3) Plasma treatment is performed with a discharge duty cycle of 1ms:200ms, with a discharge time of 60 seconds and a stop time of 30 seconds;

[0073] 4) Use an ellipsometer to measure the thickness growth curve of the silicon nitride film and calculate the film thickness growth rate.

[0074] Figure 4 The thickness growth trend and growth rate of the silicon nitride films prepared in Example 1, Example 2 and Example 5 are shown. The intermittent discharge process is more stable for controlling the film thickness growth, and the subsequent process time window can be adjusted according to demand to control the film thickness. The average thickness of 60 films from each of the two boats in Example 5 has a thickness uniformity of 2.09%

[0075] Example 6

[0076] 1) Using the silicon wafer obtained in Example 1, placing it in PECVD to deposit a double-sided amorphous silicon film;

[0077] 2) Place the sample in an annealing furnace at 880°C for 30 minutes;

[0078] 3) subjecting the sample to hydrogen injection treatment;

[0079] 4) Analyze and test the passivation performance.

[0080] Example 7

[0081] 1) Using the silicon wafer obtained in Example 1, placing it in PECVD to deposit a double-sided amorphous silicon film;

[0082] 2) Place the sample in an annealing furnace at 890°C for 30 min;

[0083] 3) subjecting the sample to hydrogen injection treatment;

[0084] 4) Analyze and test the passivation performance.

[0085] Example 8

[0086] 1) Using the silicon wafer obtained in Example 1, placing it in PECVD to deposit a double-sided amorphous silicon film;

[0087] 2) Place the sample in a tubular annealing furnace at 900°C for 30 min;

[0088] 3) subjecting the sample to hydrogen injection treatment;

[0089] 4) Analyze and test the passivation performance.

[0090] Example 9

[0091] 1) Using the silicon wafer obtained in Example 1, placing it in PECVD to deposit a double-sided amorphous silicon film;

[0092] 2) Place the sample in a tubular annealing furnace at 920°C for 30 min;

[0093] 3) subjecting the sample to hydrogen injection treatment;

[0094] 4) Analyze and test the passivation performance.

[0095] Comparative Example 3

[0096] 1) Using the silicon wafer obtained in Comparative Example 2, a double-sided amorphous silicon film was deposited in PECVD;

[0097] 2) Place the sample in a tubular annealing furnace at 880°C for 30 min;

[0098] 3) subjecting the sample to hydrogen injection treatment;

[0099] 4) Analyze and test the passivation performance.

[0100] Comparative Example 4

[0101] 1) Using the silicon wafer obtained in Comparative Example 2, a double-sided amorphous silicon film was deposited in PECVD;

[0102] 2) Place the sample in a tubular annealing furnace at 900°C for 30 min;

[0103] 3) subjecting the sample to hydrogen injection treatment;

[0104] 4) Analyze and test the passivation performance.

[0105] Comparative Example 5

[0106] 1) Using the silicon wafer obtained in Comparative Example 2, a double-sided amorphous silicon film was deposited in PECVD;

[0107] 2) Place the sample in a tubular annealing furnace at 920°C for 30 min;

[0108] 3) subjecting the sample to hydrogen injection treatment;

[0109] 4) Analyze and test the passivation performance.

[0110] Table 1 below shows the IV of Comparative Examples 3-5 and Examples 6-9. oc The data show that at an annealing temperature of 880-920°C, the passivation contact structure with oxygen-containing silicon nitride interface material performs better than the passivation contact structure with silicon oxide as the interface material, and can be used to improve the passivation effect of the battery. When the annealing temperature is 900°C, the passivation effect is the best.

[0111] Table 1 Performance comparison of passivation sheets of comparative examples 3-5 and embodiments 6-9

[0112]

[0113] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing a nano-tunneling layer, characterized in that: The following steps are involved: S1. Use an oxidizing cleaning liquid to clean the silicon wafer to produce a wet native oxide layer S2, placing the silicon wafer in a tubular PECVD quartz boat, introducing a reaction gas for heat preservation, wherein the reaction gas is a mixture of nitrogen and an oxidizing gas; S3. Continue to introduce the reaction gas to perform plasma treatment to dissociate the reaction gas, nitriding the surface of the silicon wafer to form an oxygen-containing silicon nitride film.

2. The method for preparing a nano-tunneling layer according to claim 1, characterized in that: In the steps S2 and S3, the flow ratio of nitrogen to oxidizing gas is greater than or equal to 5:

1.

3. The method for preparing a nano-tunneling layer according to claim 2, characterized in that: The oxidizing gas is selected from at least one of laughing gas, carbon dioxide and oxygen.

4. The method for preparing a nano-tunneling layer according to claim 1, characterized in that: In step S3, during the plasma discharge process, the discharge pulse time is less than 2 ms in one pulse cycle.

5. The method for preparing a nano-tunneling layer according to claim 4, characterized in that: In the step S3, the reaction pressure is greater than or equal to 140Pa.

6. The method for preparing a nano-tunneling layer according to claim 5, characterized in that: In the step S3, during the plasma discharge process, the thickness of the silicon nitride film increases by no more than 0.1 nm every 30 seconds, and its saturation thickness is less than 2.5 nm.

7. The method for preparing a nano-tunneling layer according to any one of claims 1 to 6, characterized in that: In the step S3, an intermittent discharge mode is adopted, and discharge and stop discharge are performed alternately.

8. The method for preparing a nano-tunneling layer according to claim 1, characterized in that: In step S2, the insulation temperature is 200-600° C., and the insulation time is 30-300 seconds.

9. An application of the method for preparing a nano-tunneling layer according to any one of claims 1 to 8, characterized in that: The preparation method is used for the preparation of TOPCon structure and battery.

10. The use according to claim 9, characterized in that During the preparation of TOPCon solar cells, the subsequent annealing temperature is 800-1000°C.